A 10-Year Follow-up on Arthroscopic Medial Plica Syndrome Treatments with Special Reference to Related Cartilage Injuries. (December 2021) - Paczesny, Lukasz; Zabrzynski, Jan; Kentzer, Radoslaw; Gryckiewicz, Szymon; Lewandowski, Bartosz; Szwedowski, Dawid; Kruczynski, Jacek
Objective: The aim of this study was to evaluate the factors that can affect long-term results of arthroscopic resection of medial synovial plica of the knee. Design: A total of 52 knees in 50 consecutive patients with medial plica syndrome (MPS) were enrolled to prospective study. Preoperatively the age, gender, level of activity, symptoms' duration, Lysholm knee scoring scale (LKSS), Q angle, range of motion (ROM), and quadriceps output torque (QOT) were recorded. The plica was then arthroscopically excised while plica morphological type and cartilage lesions (International Cartilage Repair Society [ICRS] classification) were registered. The postoperative evaluation was done after 1 month, 3 months, 6 months, 3 years, and 10 years. The final assessment after 10 years covered LKSS, ROM, QOT, and was enriched with functional tests: the single leg squat test (SLS), the modified Ober test (MO), and the manual palpation of the vastus medialis obliquus (VMO). Results: The mean LKSS increased from 52 (15-85, SD 16.479) preoperative to 80 (48-100, SD 15.711) at final follow-up examination. A significant negative correlation was found between LKSS and the patients' age. Cartilage lesions higher than ICRS 1 significantly decreased the final LKSS. Results were significantly better in the subgroups with normal outcome of functional tests. Conclusions: Clinical results of arthroscopic plica resection are better in patients without coexisting cartilage lesions. Poor neuromuscular control may contribute to abnormal patella tracking, leading to both medial plica irritation and further cartilage deterioration.